SOCIAL INTERACTION: RELIGIOUS COMMUNITIES IN ISLAMIC HIGHER EDUCATION - Barsihanor; Zakiyah; Galuh Nashrulah KMR; Abdul Hafiz; Siti Liani (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
The purpose of this study was to determine and analyze the forms and factors that influence social interaction between students of different religions at the Islamic University of Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin. This research uses a qualitative approach, with the type of case study research. The data in this study were extracted through in-depth interview techniques. observation, and documentation. Then the data analysis was performed using the Miles and Huberman model. The results showed that social interaction between Muslim and non-Muslim students was well adapted, their adaptive attitude would result in a desire to cooperate and help each other for the same goal, which is a cooperative associative social process, and this cooperative associative social process shapes their attitude to mutual respect for differences in beliefs which is an accommodative associative social process. Social interaction between students of different religions at UNISKA is influenced by religious learning and Islamic campus culture.